Isolation, identification, and epidemiological characteristics of goose astrovirus causing acute gout in Guangdong province, China - Yong Xiang; Meiting Chen; Minhua Sun; Jiawen Dong; Junqin Zhang; Yunzhen Huang; Qi Zhai; Ming Liao; Linlin Li (Poultry Science, 2024)
ABSTRACT: Goose astrovirus (GAstV) has been widespread in China since 2016, causing significant growth inhibition and gout symptoms in goslings and leading to substantial economic losses in the goose industry. To better understand the epidemiological characteristics of GAstV in Guangdong Province, 682 samples were collected from geese with suspected GAstV infection across different regions of Guangdong Province from January 2022 to January 2024. Virus isolation, identification, and genetic evolution analysis were performed. The results showed that all samples were GAstV positive, with 52.64% co-infected with GAstV-1 and GAstV-2, and 42.38% positive for GAstV-2 alone, indicating that GAstV-2 remains the most prevalent subtype. Additionally, three GAstV isolates were identified using molecular detection, immunofluorescence, and transmission electron microscopy on LMH cells or goose embryos. Compared with GDYJ2304 and other reported GAstV-2 strains, the ORF2 region of the GDYJ2210 isolates lacked 3 bases, and the replication ability of GDYJ2210 was significantly higher than that of GDYJ2304. Whole genome sequence alignment and genetic evolution analysis revealed that the GDFS2209 isolate was located in the GAstV-1 branch, with a sequence similarity of 89.70 to 99.00% to GAstV-1 reference strains. The GDYJ2210 and GDYJ2304 isolates were located in the GAstV-2 branch, showing a sequence similarity of 96.80 to 98.90% to GAstV-2 reference strains. These results demonstrated that the GAstV isolates were highly similar to each other despite being prevalent in 5 different regions of Guangdong Province. These findings enhance the understanding of the genetic diversity and evolution of GAstV and may facilitate the development of effective preventive strategies.